An improved model for dynamic characteristics analysis of high-contact-ratio spur gears considering localised tooth spall defect. (October 2022) - Cheng, Zhenbang; Huang, Kang; Xiong, Yangshou; Han, Guangzhi
Highlights: A hybrid model for evaluating the mesh stiffness of spalled HCRS gear is proposed. The impact of the spall bottom features on HCRS gear dynamics is investigated. Abstract: Tooth spall defects are one of the most common types of gear failures. The impact of the bottom features of the tooth spall on the dynamic properties of high-contact-ratio spur (HCRS) gears is investigated in this work. Considering the load sharing ratio, coupling structure effects, and nonlinear contact stiffness, a hybrid model was developed for evaluating the mesh stiffness of the HCRS gear, and a torsional dynamic model of the HCRS gear pair was built. The dynamic transmission errors and dynamic meshing forces are acquired by solving the above model; based on the dynamic responses of the healthy HCRS gear, the dynamic characteristics of two different spalled gear systems were compared. The results revealed that the proposed mesh stiffness model is effective within 5% calculation errors. The bottom shape of the tooth spall has important effects on the mesh stiffness but limited influence on the gear dynamic response. This study is expected to provide a theoretical foundation for future research on spall defect diagnosis in gear transmission devices.